Epigenetic disruption of miR-130a promotes prostate cancer by targeting SEC23B and DEPDC1 - Ramalho-Carvalho, João (2017)
MicroRNAs (miRNAs) are small, non-coding RNAs that mediate post-transcriptional gene silencing, fine tuning gene expression. In an initial screen, miRNAs were found to be globally down-regulated in prostate cancer (PCa) cell lines and primary tumors. Exposure of PCa cell lines to a demethylating agent, 5-Aza-CdR resulted in an increase in the expression levels of miRNAs in general. Using stringent filtering criteria miR-130a was identified as the most promising candidate and selected for validation analyses in our patient series. Down-regulation of miR-130a was associated with promoter hypermethylation. MiR-130a methylation levels discriminated PCa from non-malignant tissues (AUC=0.956), and urine samples revealed high specificity for non-invasive detection of patients with PCa (AUC=0.89). Additionally, repressive histone marks were also found in the promoter of miR-130a. Over-expression of miR-130a in PCa cells reduced cell viability and invasion capability, and increased apoptosis. Putative targets of miR-130a were assessed by microarray expression profiling and DEPD1C and SEC23B were selected for validation. Silencing of both genes resembled the effect of over-expressing miR-130a in PCa cells. Our data indicate that miR-130a is an epigenetically regulated miRNA involved in regulation of key molecular and phenotypic features of prostate carcinogenesis, acting as a tumor suppressor miRNA.